Smart biomimetic metal organic frameworks based on ROS-ferroptosis-glycolysis regulation for enhanced tumor chemo-immunotherapy - Yang, Jie; Ma, Siyu; Xu, Rui; Wei, Yawen; Zhang, Jun; Zuo, Tiantian; Wang, Zhihua; Deng, Huizi; Yang, Ning; Shen, Qi (Journal of controlled release, 2021)
Antitumor immunotherapy is limited by low tumor immunogenicity and immunosuppressive microenvironment (TIME), which could be improved by “ROS-ferroptosis-glycolysis regulation” strategy. Herein, a cancer cell membrane coated metal organic framework (MOF) loading with glucose oxidase (GOx) and doxorubicin (DOX) was constructed (denoted as mFe(SS)/DG). Benefiting from the homotypic targeting of cancer cell membrane, the nanoplatform effectively accumulated in tumors. mFe(SS)/DG based on coordination between Fe3+ and disulfide-bearing ligand scavenged GSH and downregulated glutathione peroxide 4 (GPX4) to trigger ferroptosis. GOx catalyzed glucose to generate abundant H2O2 for enhancing Fenton reaction, resulting in excessive ROS in tumors. The ROS burst simultaneously promoted ferroptosis and inhibited glycolysis. Ferroptosis combined with DOX induced immunogenic cell death (ICD) and released tumor antigens to initiate antitumor immunity. Glycolysis repression remodeled TIME by decreasing lactate to solidify and boost the antitumor immunity. The smart biomimetic nanoplatform integrates tumor metabolism and immunity based on ROS-ferroptosis-glycolysis regulation, providing a potential anti-tumor strategy. [Display omitted]